Quantifying phenological asynchrony of phyto- and zooplankton in response to changing temperature and nutrient conditions in Lake Müggelsee (Germany) by means of evolutionary computation. (December 2021) - Recknagel, Friedrich; Adrian, Rita; Köhler, Jan
Abstract: There is a need to determine and quantify global change induced phenological asynchrony because of possible loss of biodiversity and implications for the food web. Phenological asynchrony in freshwater lakes can be studied retrospectively by analysing historical data, and prospectively by scenario analysis based on historical data. Models allowing to study phenology by scenario analysis need to be valid for multiple populations over decades limiting the suitability of process-based models that are structural rigid and calibratable only for a limited period of time. Here we applied models inferred from historical data by evolutionary computation to simulate food-web dynamics of the plankton community of Lake Müggelsee from 2002 to 2012. The models were driven by nutrient concentrations, water temperature (WT) and endogenous interrelationships within the plankton community. The validated models simulated seasonal and inter-annual dynamics of seven phyto- and zooplankton groups in response to scenarios of prospective global warming, nutrient enrichments as well as combinations of warming with nutrient enrichments and warming with nutrient reductions. Phenological WT-sensitivities resulting from the warming scenario indicated substantial shifts towards earlier timing of cyanobacteria peaks and delayed timing of cladocerans peaks in summer, suggesting significant phenological asynchrony in the plankton community of Lake Müggelsee. The phenological sensitivities of cyanobacteria and cladocerans towards phosphorus and nitrogen enrichments revealed similar trends of summer peaks as identified for warming, most likely contributing to phenological asynchrony. The combination of warming and nutrient reductions showed increased spring maxima but almost unchanged summer peaks of cyanobacteria demonstrating that gradually decreasing phosphorus and nitrogen concentrations may outweigh warming effects on phytoplankton growth. Scenarios that simulated WT- and nutrient-changes as gradual processes rather than immediately imposed events proved to be more realistic and credible. The proposed ensemble of complementary inferential models proved to be a viable tool for determining long-term dynamics and phenological asynchronies in plankton communities under the impact global changes. Highlights: Inferential modelling of long-term plankton dynamics of Lake Müggelsee by evolutionary computation suitable for scenario analysis on impacts of global warming and eutrophication. Applying the scenario analysis for determining phenological asynchrony within the plankton community in response to gradually changing environmental conditions. Deriving and analysing phenological sensitivities of phyto- and zooplankton from scenarios on warming and nutrient enrichment.